Uppfölining av naturvårdande skötselåtgärder(NS) i ekopark Storklinten - Emanuelsson, Gabriel (2014)
This study's primary purpose was monitoring of conservancy operation measures. The fixed sections within ekopark Storklinten owned by the forest company Sveaskog. These measures are performed with the purpose of creating and maintaining hardwood forest and mimic natural processes. The sections were divided into different categories depending on the type of measures they were exposed with. The monitoring showed that the purpose of these measures was fulfilled in general. In the future it should be taken in mind on how continued operation should be performed and what experience that can be taken from the already performed measures.